Comments on the Pyridine Catalyzed Reaction of Alcohols with Lead Tetraacetate in Benzene Containing 1% Acetic Acid (v/v) - K. Banerjee, Sudheer; Shankar, R. (Asian Journal of Chemistry, 2010)
The role of pyridine in catalysis, as ligand or proton abstracting base, in the lead tetra-acetate oxidation of alcohols has been evaluated using a novel molecular geometry (and kinetics) approach.